Removal of residual oil from palm oil mill effluent (pome) by reverse osmosis membrane / Norliza Ibrahim and Abdul Latif Ahmad - Ibrahim, Norliza; Ahmad, Abdul Latif (2004)
Malaysia is one of the largest producers of palm oil. Most of the palm oil processing is carried out in palm oil mills where oil is extracted from palm oil fruit bunch. Two sources of oil from fruit bunch are fleshy mesocarp of fruit (45-55% oil) and kernels (50% oil). It is estimated that for every tonne of fruit bunch processed produces 1.5 tonne of palm oil mill effluent (POME) POME is a mixture of sterilizer condensate, separator sludge and hydrocyclone wastewater. Fresh POME is a colloidal suspension of 95 - 96 % water, 0.6 - 0.7 % oil and 4 - 5 % total solids including 2 - 4 % suspended solids which is mainly debris from palm fruit mesocarp. It is acidic (pH 4-5), hot (80 90°C) and contains high amount of total solids (40 500 mg/I) and oil (4000 mg/l). POME was first pretreated to remove the high content of suspended solids and residual oil using flocculation, solvent extraction and adsorption processes. Lastly C-series membrane was used to remove any residual oil remaining after the pretreatment processes. Operating pressure and pH were varied in order to find the optimum conditions for membrane separation process. It was found that the optimum removal of residual oil was achieved at a system pressure of 10 bars and pH 9. At these conditions, the oil concentration was decreased from 100 mg/l to 51 mg/l after 30 min of filtration.